2013
DOI: 10.1080/09593330.2013.808251
|View full text |Cite
|
Sign up to set email alerts
|

Modified batch anaerobic digestion assay for testing efficiencies of trace metal additives to enhance methane production of energy crops

Abstract: Batch biochemical methane potential (BMP) assays to evaluate the methane yield of biogas substrates such as energy crops are usually carried out with undiluted inoculum. A BMP assay was performed on two energy crops (green cuttings and grass silage). Anaerobic digestion was performed both with and without supplementation of three commercial additives containing trace metals in liquid, solid or adsorbed form (on clay particles). In order to reveal positive effects of trace metal supplementation on the methane y… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
1

Year Published

2014
2014
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(7 citation statements)
references
References 73 publications
0
6
1
Order By: Relevance
“…4). This result did not confirm the outcomes of previous works (Karlsson et al 2012;Brulé et al 2013) in which trace elements were pointed out to influence anaerobic degradation. Actually, in this experimentation, the tested substrates in the vessels were highly diluted; thus, it can be supposed that trace element content in the inoculum was enough for enabling anaerobic degradation process.…”
Section: Batch Testscontrasting
confidence: 80%
“…4). This result did not confirm the outcomes of previous works (Karlsson et al 2012;Brulé et al 2013) in which trace elements were pointed out to influence anaerobic degradation. Actually, in this experimentation, the tested substrates in the vessels were highly diluted; thus, it can be supposed that trace element content in the inoculum was enough for enabling anaerobic degradation process.…”
Section: Batch Testscontrasting
confidence: 80%
“…For the two setups including dilution, after the addition of inoculum and substrate, either distilled water or nutrient/buffer solution was added to reach 400 mL; the corresponding blank samples contained inoculum diluted with distilled water or nutrient/buffer solution respectively. The nutrient/buffer solution was prepared according to Brulé et al (2013). For each series, five different substrate loads at a fixed ISR of 2 (based on VS) were studied.…”
Section: Methodsmentioning
confidence: 99%
“…growth (Angelidaki and Sanders, 2004;Raposo et al, 2012). It has also been shown that additions of these types of medium improve the methane potential of diluted inocula while undiluted ones are not affected (Brulé et al, 2013). Nonetheless, there are few guidelines recommending what substrate concentration to use in a BMP test to reach optimal results.…”
Section: Introductionmentioning
confidence: 97%
“…[27] Thus, lack of trace elements could result in reduced biogas production in mono-digestion plants without manure addition, depending on the type of the energy crop used, and furthermore, too high amounts could also pose adverse impacts and cause severe problems as well. [6,8,[28][29][30] Some energy crops may be lacking these trace metals, such as maize silage used in this study for Co and Ni, or alfalfa silage for Co. [30] Therefore, both macro-and micronutrient supplementation for monodigestion of maize and sugar beet silage [31,32] or for energy crop mixtures (sugar beet, maize and triticale) [33] is strongly recommended to attain high methane yields at short hydraulic retention times along with low volatile fatty acid production. In this work, in addition to the adequate C/N ratio already available in the substrate (Table 1), [34] the amount of trace metals supplemented seemed to provide higher methane yields and a stable digestion period as indicated by steady biogas and methane production values accompanied by neutral pH range in batch digesters.…”
Section: Methane Yields Obtained From Maize Silage By Ni Co and Mo Smentioning
confidence: 98%